Formative interventions and practice-development: A methodological perspective on teacher rounds. (2015) - Ellis, Viv; Gower, Cathy; Frederick, Kenny; Childs, Ann
Abstract : Highlights: We examine Rounds in education from a methodological perspective. In doing so, we class Rounds as a formative intervention and compare it to another means of formative intervention—Developmental Work Research. We raise three methodological issues about both types of formative intervention: the role of theory; the relationship between the individual and the collective; and the meaning of collaboration.